THE IMPLICATION OF SAM'IYYAH SHAFAWIYAH METHOD IN LEARNING ARABIC LANGUAGE TOWARDS STUDENTS' MASTERY OF MUFRODAT - Maul, Rin Bidah (Armala, 2024)
This research will discuss the description and explanation of the sam'iyyah syafawiyah method in improving students' mastery of mufrodat in learning Arabic. The aim of this research is to provide results and evidence to the community that the sam'iyyah syafawiyah method is effective. This research is included in literature study research. Library research is used to obtain research data, namely in the form of the sorogan method to increase students' interest and self-confidence. The results obtained regarding the sam'iyyah syafawiyah method technique are practiced by drilling until students are able to master mufrodat.